Dissecting long-term Bund yields in the run-up to the ECB’s public sector purchase programme - Lemke, Wolfgang; Werner, Thomas (Journal of Banking & Finance, 2020)
In the run-up to the ECB’s public sector purchase programme in March 2015, German government bond yields declined significantly. Using an affine term structure model, we provide evidence that the yield declines are almost fully attributable to a decline in the term premium as opposed to the expectations component. This speaks in favour of a portfolio re-balancing channel being at work rather than a (policy rate) signalling channel. The result proves robust against changing the number of factors in the model, the estimation sample and the estimation approach.